Impact of COVID-19 On Nepalese Economy - Karn, Santosh Kumar (International Journal of Social Sciences and Management, 2021)
The worldwide pandemic of COVID-19 has caused human losses and severely affected the global economy and passing in a turmoil situation. The COVID 19 pandemic is having a significant economic as well as health impact in Nepal. The economy of Nepal is also grappled by the severe public health crisis of the Covid19. As the public health emergency is heavily interconnected with economic affairs, it has impacted each of the pillars of the economy. This article focuses on COVID19 impact on economic growth in Nepal. The main purpose of this paper is to make evaluations of the potential impact of the COVID-19 pandemic on the economy of Nepal has resulted in historically the highest agriculture, remittance unemployment and biggest fall in GDP. Int. J. Soc. Sc. Manage. Vol. 8, Issue-2: 348-351